The rock-cut archaeological complex of Yelpin-1, Vayots Dzor Province, Armenia - Dan, Roberto; Gasparyan, Boris; Vitolo, Priscilla; Petrosyan, Artur; Saccone, Tommaso; Nahapetyan, Samvel; Adigyozalyan, Ani; Moradi, Ghasem; Zecchi, Chiara (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
This article describes some of the archaeological activities carried out as part of the Vayots Dzor Project (VDP), an Armenian – Italian archaeological expedition aimed at a detailed investigation of Vayots Dzor Region. The project is based on a Memorandum of Understanding between the Institute of Archaeology and Ethnography of the National Academy of Sciences of the Republic of Armenia (IAE NAS RA) and ISMEO – International Association of Mediterranean and Oriental Studies. The expeditions are co-financed by Gfoeller Renaissance Foundation of USA, ISMEO and MAECI (Ministry of Foreign Affairs and International Cooperation of the Italian Republic, ARC-001548).